Evaluasi terhadap Sistem Pengendalian Intern pada Proses Pemberian Kredit Mikro Koperasi Simpan Pinjam (KSP) - Jauharatul Maknun (COSTING : Journal of Economic, Business and Accounting, 2019)
Cooperative is a joint business entity engaged in the economy, consisting of those who berekotakan weak voluntarily joined and the equality of rights, is obliged to undertake a business that aims to meet the needs - the integrity of its members. Cooperative Artha Makmur is a keuhangan institution that collects funds from the community in the form of savings and menyerhkannya back in the form of credit. In the implementation of the provision of microcredit, the risk of credit congestion is a problem that is often faced by co-operatives and negatively affect the cooperative one of them inhibit the rate of credit turnover and disrupt the performance of management. Bad credit itself occurs due to too lax lending and internal control system is also still not in accordance with the theory and has not been implemented optimally. Therefore the authors took the initiative to evaluate the internal control system of credit giving to the cooperative Artha Makmur. The evaluation result shows that the system applied in the crediting process has largely fulfilled the elements of internal control, although there are still weaknesses, namely the Internal Control System in the Artha Makmur cooperative has not been evident so that in the fear of loss caused by the weak credit quality. In addition, on the spot implementation is done, not in accordance with the manual procedure of microcredit products. Keywords: Internal Control System, Cooperative, Credit Granting